Morphological changes in spectral domain optical coherence tomography guided bevacizumab injections in wet age-related macular degeneration, 12-months results - Michalewski, Janusz (Medknow Publications & Media Pvt Ltd, 2014)
PURPOSE: To describe retinal changes during Spectral Domain Optical Coherence Tomography (SD-OCT) guided bevacizumab treatment for neovascular age- related macular degeneration (AMD). SETTINGS AND DESIGN: Single center observational study. MATERIALS AND METHODS: We confirmed wet AMD in 47 eyes of 45 patients by fluorescein angiography and SD-OCT. After bevacizumab injection, we examined the patients at 4-week intervals. During each follow-up control, we performed SD-OCT and a complete ophthalmic examination. Criteria for reinjection were visual acuity loss of more than five ETDRS letters, and/or increase of central retinal thickness, sub-retinal fluid, intra-retinal fluid, pigment epithelium detachment. If reinjection criteria were not met, we advised the patient to return in 4 weeks’ time for the next scheduled follow-up. We used 3-dimensional SD-OCT to measure photoreceptor defects and sub-retinal fibrosis. The main efficacy endpoints were the SD-OCT measurements of the size of photoreceptor defects, the size of external membrane defects and the central retinal thickness. RESULTS: Over the 12 months study period, the percentage of scans in 3-D imaging mode showing visible defects of the junction between inner and outer segments of photoreceptors increased from 38.96 to 53.8%. The percentage of scans in 3-D imaging mode with visible sub-retinal fibrosis increased from 33 to 52% and mean central retinal thickness decreased from 333 μm (96-900 μm) to 272 μm (P = 0.011). CONCLUSION: In long-term anti- Vascular endothelial growth factor (VEGF) treatment for neovascular AMD, photoreceptor defects and fibrosis progress despite a decrease in central retinal thickness and improvements in visual acuity. We would encourage further discussion as to whether this is the natural course of the disease or a result of the treatment.